Розвідки на території с. Комарове у 2009 р. - Охріменко, В.Г.; Баюк, В.Г. (Археологічні дослідження в Україні, 2010)
Results of archaeological prospecting in 2009 in Komarove village of Manevychi Region in Volyn Oblast are presented. The existence of settlements of the Bronze Age, Ancient Rus period and the Late Mediaeval times is confirmed.